The role of hepcidin in iron metabolism - Adamska-Tomaszewska, Dagmara; Więcek, Sabina (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Iron is an essential mineral component of the human body, and its deficiency leads to impaired function of many important systems. One of the elements controlling the bioavailability of dietary iron is the concentration of hepcidin in blood serum. Hepcidin is an acute phase protein produced mainly by hepatocytes. Its production is regulated by proinflammatory cytokines and by the activation of cellular pathways by the soluble transferrin receptor (TtF) in response to increased iron concentration. The basic role of hepcidin is reducing the absorption of dietary iron in enterocytes by changing the conformation of ferroportin and influencing its ubiquitination. Ferroportin plays a role in the release of iron ions by macrophages. Due to the important role of the hepcidin-ferroportin axis in the development of anemia in patients with chronic inflammatory diseases, it has been the focus of numerous studies seeking new therapeutic strategies for patients with chronic anemia.